Pengaruh Kelembapan Tanah terhadap Kelimpahan Cacing Tanah (Lumbricidae) di Coban Putri - Fany Aura Shabrina; Ibing Mustika Jingga; Innaisya Saundra Arsy; Nuzula Alfa Farikhah; Muhtizar Zamrut; Khayla Anatasya; Merisa Eka; Indra Fardhani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Earthworms are important organisms in the soil ecosystem that play a role in improving soil structure and accelerating the decomposition of organic matter. This study aims to analyze the relationship between soil moisture and the abundance of earthworms (Lumbricus sp.) in the Coban Putri area, Batu City. The method used is descriptive quantitative with a field survey approach through a quadratic plot technique in 30 observation plots divided into three locations based on the distance from the waterfall. Soil moisture was measured using a soil moisture meter with an index scale of 1-10, while the abundance of earthworms was calculated based on the number of individuals in each plot measuring 50x50 cm with a depth of 20 cm. The results showed an average soil moisture of 6.2 and an average abundance of earthworms of 3.5 individuals per plot. Locations near the waterfall had the highest humidity (7-8) with 3-6 individuals of worms per plot, while locations far from the waterfall had the lowest humidity (4.5-5.5) with only 1-3 individuals of worms per plot. Spearman's correlation analysis showed an r value of 0.277 with a p value of 0.139, indicating a weak positive relationship between soil moisture and earthworm abundance and not statistically significant. Soil moisture plays a role in supporting earthworm presence, but their abundance is also influenced by other environmental factors, such as soil pH, temperature, and organic matter content.